CHEMICAL PROFILING AND ANTIBACTERIAL ACTIVITY OF Nannochloropsis oculata EXTRACTS AGAINST FOODBORNE PATHOGENS - Hati, Futi Kusuma; Nurjayadi, Muktiningsih; Kartika, Irma Ratna; Azahra, Nur Fadillah Adelia; Albana, Fadhila Shofi; Aisyafitri, Afifah; Aurellia, Dema Griseldis (Lantanida Journal, 2026)
Foodborne illnesses remain a public health concern in Indonesia, prompting the search for natural antibacterial agents. This study evaluated the antibacterial activity and chemical profile of Nannochloropsis oculata extracts against Listeria monocytogenes and Shigella flexneri. Microalgae were cultivated, and cell density was monitored using an Ultraviolet–Visible (UV–Vis) spectrophotometer. Biomass was harvested and extracted using chloroform–methanol, followed by compound identification through Gas Chromatography–Mass Spectrometry (GC–MS). Antibacterial activity was assessed using the disc diffusion method. A total of 1.3196 g of dry biomass was obtained. At 200 mg/mL, the extract produced inhibition zones of 8.40 ± 0.17 mm against L. monocytogenes and 8.83 ± 0.29 mm against S. flexneri. GC–MS analysis revealed fatty acid derivatives, predominantly methyl palmitoleate (26.47%). These findings provide preliminary insight into the antibacterial potential of N. oculata extracts; however, further quantitative and application-based studies are required to determine their practical relevance.